Perancangan Kemasan Produk Amplang Berbasis Preferensi Konsumen Di Kabupaten Ketapang - Oktavia Omi Rani; Nurimansyah Nurimansyah; Ira Arianti; Irfan Cholid; A. Nova Zulfahmi (Jurnal Riset, Inovasi, Teknologi & Terapan, 2026)
Packaging is an important factor influencing consumer perceptions and purchasing decisions for food products. This study aimed to identify consumer preferences for the packaging design of amplang products in Ketapang Regency as a basis for developing packaging designs that better meet market needs. The research employed a quantitative descriptive method using a survey approach involving 39 respondents selected through non-probability sampling with purposive-accidental sampling techniques. Data were collected through structured questionnaires and analyzed using descriptive statistics, including percentages, mean scores, and Likert scale index analysis. The results showed that packaging plays a highly important role in purchasing decisions, with an index value of 88.2%. The highest-rated packaging attributes were the ability to maintain product crispness (89.2%), protect the product (86.3%), and environmental friendliness (85.6%). The main weaknesses of current amplang packaging were incomplete product information (48.7%) and insufficient airtightness (25.6%). Consumers preferred medium-sized standing pouch packaging (87.2%) with neutral colors (59.0%). In addition, product information was identified as the highest priority in packaging design, followed by packaging strength and attractive visual design. Based on these findings, the recommended packaging design for amplang is a medium-sized standing pouch that is informative, durable, practical, environmentally friendly, and capable of preserving product quality and crispness. The findings are expected to serve as a reference for small and medium enterprises (SMEs) in improving the competitiveness and added value of amplang products.